Acid-catalyzed allenylation of pyrazolones with propargyl alcohols. Issue 22 (19th May 2021) - Zhang, Wande; Wei, Shiqiang; Qu, Jingping; Wang, Baomin
Abstract : A TsOH-catalyzed allenylation of pyrazolones with propargylic alcohols has been developed. The established reaction system is well tolerated by a wide scope of pyrazolones and propargylic alcohols. Abstract : A TsOH-catalyzed allenylation of pyrazolones with propargylic alcohols has been developed. The established reaction system is well tolerated by a wide scope of pyrazolones and propargylic alcohols. The process has the salient features of operational simplicity, facile scale-up and high yield. In particular, the integration of the pharmaceutical-related pyrazolone skeleton and the allenyl group into a single molecule not only enriches the structural diversity of the pyrazolone scaffold, but potentially also contributes to a broader spectrum of biological activity. Furthermore, it is easy to synthesize 3aa in gram-scale with the yield and efficiency basically maintained, making the practical application of this process more prominent.